Highly replicating hepatitis C virus variants emerge in immunosuppressed patients causing severe disease - Lohmann, Volker; Rothhaar, Paul; Heuss, Christian; Tulessin, Margaret; Wang, Zhiqing; Seong, Thomas; Förster, Colin; Quistrebert, Jocelyn; Chai, Haiting; Reineke, Marvin; Benning, Louise; Honegger, Jonathan; et al. (Research Square, 2025)
Hepatitis C virus (HCV) exists as a heterogenous quasispecies, but the phenotypic consequences of viral variability are widely unexplored. Here we identified a replication enhancing domain (ReED) in nonstructural protein 5A conferring high replication fitness to clinical isolates. Accumulation of mutations in the ReED mediates high genome replication capacity. In a cohort of liver transplant patients, high replicator variants were exclusively found in individuals with severe disease outcome, suggesting that high viral replication fitness is associated with increased viral pathogenesis. Analysis of large sequence cohorts revealed that overall only 10% of viral genomes showed genetic signatures of high replicators, which were enriched in recipients of liver transplantations, patients developing hepatocellular carcinoma and in HIV coinfected individuals. Overall, our data suggests that low replication fitness is a hallmark of HCV, contributing to establishment of persistence, whereas high replicators appear to have an advantage under conditions of immune suppression, thereby enforcing pathogenesis.